The efficacy of some local isolates of the fungus Beauveria bassiana (Bals.) Vuil. on The tomato leaf miner, Tuta absoluta (Meyrick) Larvae (Latakia University Journal -Biological Sciences Series, 2023)
The tomato leaf miner, Tuta absoluta  is among the most destructive pests that attack tomato in many countries. In this study, the efficiency of three suspensions (2×104, 2×106 ,2×108 spore/ml) of four different local isolates (b6, b7, b8, b10) of the entomopathogenic fungus Beauveria bassiana was investigated against  T. absoluta larvae 1fr,2nd, 3rd and 4th instar under laboratory condition for eight days to study the effect of these isolates  at that  different concentration  on larval mortality .  The results showed significant differences of mortality rate among the isolates themselves as well as between them and the control treatment. Corrected mortality rates at the highest concentration (2×108 spore/ml) were (71.85، 60، 68.89، 58.89%) for b6 isolate  and (60.74، 49.63، 58.52، 58.15%) for b7 isolate, and (100، 100، 92.9، 89.63%) for b8 isolate and for b10 isolate were (100, 96.30, 96.67, 92.96%) on 1fr,2nd, 3rd and 4th instar larvae, respectively. The LT50 for four isolates at the same concentration was 4.9, 5.8, 4.7, 6.4 days for b6 isolate and 5.7, 7.5, 6.7, 6.2 days for b7 isolate and 3.2, 3.4, 3.8, 3.9 days for b8 isolate, and for b10 isolate was 3.4, 3.6, 3.7 and 3.7 days for 1fr,2nd, 3rd and 4th instar larvae, respectively. While the LC50 values  were ( 4 x 104, 4 x 106, 1 x 106, 4 x 106 spore/ml) for b6 isolate, (2 x 106, 5 x 108, 7 x 105, 2 x 107 spore/ml) for b7 isolate, (2 x 104, 3 x 104, 2 x 103, 3 x 103 spores/ml) for b8 isolate, (2 x 104, 3 x 103, 3 x 103, 5 x 104 spores/ml) for b10 isolate on 1fr,2nd, 3rd and 4th instar larvae, respectively.